Hope in the unknown: The relationship between intolerance of uncertainty, hope, and anxiety - Coscolluela, Isabel Victoria Ledesma (Animo Repository, 2016)
The goal of this study was explore the relationship between intolerance of uncertainty, hope and anxiety. A final sample of 236 undergraduate students from two Philippine universities was recruited. The participants answered a questionnaire to measure their levels of intolerance of uncertainty, hope, and anxiety, and underwent an induction of anxiety task. The interaction between intolerance of uncertainty was found to interact with trait hope to account for the variance in state anxiety. In additional analyses, the components of both hope (agency and pathways) and intolerance of uncertainty (inhibitory and prospective) were analyzed. An interaction of high trait agency and high intolerance of uncertainty was associated with lower levels of trait anxiety. For state anxiety, an interaction between high hope and high inhibitory intolerance of uncertainty was associated with higher levels of state anxiety. Findings of this study suggest that intolerance of uncertainty does not necessarily mean a negative outcome when there is a high level of hope. There is also a difference in its effects between trait and state anxiety. Intolerance of uncertainty and hope are potential targets for interventions in individuals dealing with anxiety.